18F-fluoride PET/CT for bone scanning - Nagarajah, J.; Dannat, T.; Hartung, V.; Bockisch, A.; Rosenbaum-Krumme, S. (Nuklearmedizin - NuclearMedicine, 2012)
Aim:18F-fluoride PET/CT is a promising tool for bone scanning. Recently, guidelines concerning the conduct of 18F-fluoride PET/CT have been published. One open question of the German guideline was the necessity of attenuation correction for 18F-fluoride PET/CT. We evaluated the need for a CT-based attenuation correction in 18F-fluoride PET/CT scans for the detection of bone lesions. Patients and methods: We retrospectively analyzed wholebody 18F-Fluoride PET/CT scans of 59 cancer patients. The lesions were categorized as malignant, benign or inconclusive. This assignment was performed for every lesion in both: attenuation corrected (AC) and non-attenuation- corrected (NAC) images. The maximum standardized uptake values (SUVmax) of the lesion in the AC images were also determined. Results: All bone lesions were detected in both image modalities. The AC images revealed 201 lesions categorized as malignant, 114 as benign and 35 as inconclusive. Without an AC, the results were 209, 116 and 25, respectively (p > 0.05). 10/35 lesions categorized as inconclusive in the AC images were categorized as malignant in the NAC images, whereas 8 lesions were confirmed after comparison with other imaging modalities and follow-up data and 2 lesions were categorized as benign. The SUVmax for lesions identified as malignant showed a broad overlap with the SUV max of benign lesions and can consequently not be used for differentiation. Conclusion: An AC is not necessary for detecting bone lesions on 18F-fluoride PET/CT scans as the detection capability is identical for NAC imaging and lesion assignment was even better than with AC imaging. SUVmax seems not to improve the differentiation between malignant and benign bone lesions.
Keywords: 18F-fluoride PET/CT; bone scanning; bone lesion; attenuation correction